'Sailing in troubled waters': a review of the use of anticoagulation in adult cancer patients with thrombocytopenia. Issue 6 (September 2016) - Ibrahim, Rami B.; Skewes, Michelle D.; Kuriakose, Philip
Abstract : Simply providing anticoagulation therapy is not as straightforward of a solution in cancer patients who have concurrent thrombocytopenia owing to the increased risk of bleeding complications. Currently, few guidelines are in place to assist clinicians in safely managing thrombocytopenic cancer patients on anticoagulation. The purpose of this review is to critically examine the available body of biomedical literature surrounding anticoagulant use against the backdrop of cancer-related thrombocytopenia in adult patients. Available evidence for the use of parenteral anticoagulants (low molecular weight heparins, unfractionated heparin, pentasaccharides, and direct thrombin inhibitors) and oral anticoagulants (vitamin K antagonists and novel oral anticoagulants) in thrombocytopenic cancer patients is described. The review revealed many inconsistencies between reports on this topic, which made it difficult to draw firm conclusions as to, for example, the ideal well tolerated anticoagulant dose in thrombocytopenic cancer patients? Intriguingly, critical clinical information including (but not limited) patient platelet nadirs, platelet counts during bleeding episodes, and platelet transfusion support was absent from a not-so-insignificant number of publications. Despite these shortcomings, the review sets out to formulate recommendations on the management of anticoagulation, at prophylactic or treatment doses, in adult cancer patients who also have concurrent thrombocytopenia. It also enlists a call for the medical community, by mapping select clinical guideposts, for further research in this setting. With the inclusion of these criteria in future studies, only then formal recommendations on the ideal safe dosage of anticoagulants in cancer patients, based on solid evidence, are conceived.